Molecular basis of cold adaptation. - D'Amico, Salvino (2002)
Cold-adapted, or psychrophilic, organisms are able to thrive at low temperatures in permanently cold environments, which in fact characterize the greatest proportion of our planet. Psychrophiles include both prokaryotic and eukaryotic organisms and thus represent a significant proportion of the living world. These organisms produce cold-evolved enzymes that are partially able to cope with the reduction in chemical reaction rates induced by low temperatures. As a rule, cold-active enzymes display a high catalytic efficiency, associated however, with a low thermal stability. In most cases, the adaptation to cold is achieved through a reduction in the activation energy that possibly originates from an increased flexibility of either a selected area or of the overall protein structure. This enhanced plasticity seems in turn to be induced by the weak thermal stability of psychrophilic enzymes. The adaptation strategies are beginning to be understood thanks to recent advances in the elucidation of the molecular characteristics of cold-adapted enzymes derived from X-ray crystallography, protein engineering and biophysical methods. Psychrophilic organisms and their enzymes have, in recent years, increasingly attracted the attention of the scientific community due to their peculiar properties that render them particularly useful in investigating the possible relationship existing between stability, flexibility and specific activity and as valuable tools for biotechnological purposes.